DESIGN AND SIMULATING TWO INPUT CONVERTER AND TESTING THE PV PANEL PSPICEMODEL - Kubba, Zainab M; Samair, Zaid (Al-Nahrain Journal of Science, 2010)
This paper deals with the design and simulation of two input converter. The first input is aphotovoltaic module and the other is a battery. The photovoltaic module was represented as theequivalent circuits implemented in ORCAD PSPICE program; the use of equivalent circuit makes itpossible to investigate the characteristics of a PV module. The waveforms obtained from transientsimulation of buck converter for different modes of operation boundary, continuous anddiscontinuous are presented. The results of the converter simulation with PV model show a goodagreement to that measured by battery.